PENGEMBANGAN BUKU SUPLEMEN BAHASA INDONESIA BERBASIS BUDAYA LOKAL MENGGUNAKAN MODEL CIRC UNTUK SISWA SEKOLAH DASAR - Azizah, Lutfia Nur (Jurnal Pena Karakter (Jurnal Pendidikan Anak dan Karakter), 2019)
The general objective of this study is to develop an Indonesian supplementary book based on local culture in Ponorogo Regency using CIRC model. This development research refers to the ADDIE model which consists of stages (1) Analysis; (2) Design; (3) Development; (4) Implementation; (5) Evaluation. Data collection techniques were carried out by documentation techniques, validation techniques, observation techniques, questionnaires, and tests. The supplement book trial was conducted twice with limited trials dan extensive trials. The results of this study indicate that the average percentage of book validation is 96,2% which means the quality are very high. The responses of teacher and students to the use of supplementary books were 91,7% and 85%. The result of the comparison of limited trials show the value of tcount = 5.118 > ttable = 2.365 which means Ho is rejected. Similarly, the results of the comparison of extensive trials show that the value of tcount = 10.514 > ttable = 2.365, which means Ho is rejected.